Peranan Mediasi Informal dalam Penyelesaian Sengketa Tanah di Desa Sungai Jior menurut Kompilasi Hukum Islam - Erwin Hamonangan Pane; Hadisah Mardiah Nasution; Nur Hakima Akhirani Nasution (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the implementation of informal mediation in resolving land disputes among heirs in Sungai Jior Village, the role of informal mediation from the perspective of the Compilation of Islamic Law, and the supporting and inhibiting factors in its implementation. This study employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with religious leaders, traditional figures, the village head, and parties involved in informal dispute resolution. The findings reveal that informal mediation in Sungai Jior Village is conducted in a familial manner, involving religious and traditional leaders as mediators. Agreements are reached orally and are considered morally and traditionally binding. This mediation plays an essential role in preventing prolonged conflicts, restoring family relationships, and achieving a fair inheritance distribution in accordance with Islamic principles as stipulated in the Compilation of Islamic Law. Supporting factors include trust in community leaders, a strong culture of deliberation, and process efficiency, while inhibiting factors involve emotional unpreparedness of disputing parties and the absence of clear inheritance documents